The Role of Metabolic Testing in the Diagnostic Evaluation of Adult NORSE: A Retrospective, Single‐Centre Study - Kilmer, Jennifer; Ransley, George; Murphy, Elaine; Hanna, Michael G.; Pitceathly, Robert D. S.; Rajakulendran, Sanjeev; Pizzamiglio, Chiara (European journal of neurology, 2025)
ABSTRACT Background New‐onset refractory status epilepticus (NORSE) is a diagnostically challenging and severe epileptic presentation in which aetiology is an important predictor of outcome. This retrospective study aimed to investigate the utility of metabolic screening to determine the underlying cause in 42 patients with suspected NORSE, admitted to The National Hospital for Neurology and Neurosurgery, London, between 2004 and 2021. Methods Demographic, clinical, biochemical, and molecular data were collected. Sixty‐two per cent of the cohort was classified as cryptogenic (cNORSE), while 38% had symptomatic NORSE (sNORSE). Results Despite extensive investigations (100 metabolic‐related tests were performed among the 42 cases), inherited disorders of metabolism were not identified as causes for NORSE. Nevertheless, three patients with refractory status epilepticus (RSE), who did not fulfill the diagnostic criteria for NORSE, had a primary mitochondrial disease (PMD). These data help establish criteria that distinguish PMD‐related RSE from cNORSE, including pre‐existing multisystemic features, a positive family history and/or suggestive MRI findings. Conclusion The study highlights the challenges in diagnosing NORSE aetiology and the limited utility of extensive testing for inherited metabolic disorders in this patient population. Further research is required to refine diagnostic strategies and enhance our understanding of the heterogeneous aetiology of cNORSE.